The Equity Risk Premium and the Required Share Returns in a Tobins q Model - Jakob B. Madsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
Based on the Tobins q principle this paper shows that earnings per unit of capital and the output capital ratio are excellent measures of the required share returns because they are only temporarily affected by earnings shocks but are driven permanently by changes in required share returns. Evidence for the US over the period from 1889 to 2002 suggests that real required share returns and the equity risk premium climbed to extraordinarily high levels from the late 1930, to the end of the 1940s, and have since declined. The risk premium is currently somewhere between 4 and 6%.
Keywords: G12; E22; E44; 330; expected share returns; equity risk premium; Tobins q; share valuation; macroeconomic factors; Risikoprämie; Tobin's Q; Makroökonomischer Einfluss